TITLE: COMPARATIVE ANALYSIS OF INTERCULTURAL COMMUNICATION: GESTURES IN SLOVAK, AMERICAN, AND UZBEK CULTURES - Uktamova Ozodakhon Ilhomjon kizi (TADQIQOTLAR.UZ, 2024)
This thesis examines the role of gestures in intercultural communication across Slovak,  American,  and  Uzbek  cultures.  Focusing  on  both  common  and  culturally unique gestures, the study identifies how gestures reflect  each culture’s underlying values  and  communication  norms.  Using  interviews  and  observational  data,  the findings reveal that while American gestures are often open and expressive, Slovak gestures  tend  to  be  more  restrained,  and  Uzbek  gestures  emphasize  respect  and hierarchy.  These  differences  have  implications  for  effective  cross-cultural communication and understanding in increasingly globalized interactions.